Application of electric arc wire feeding process in preparation of aero-engine turbine disc material

By combining arc wire feeding technology with ultrasonic assistance and nanoparticle composite multi-directional micro-forging, the problems of coarse material structure, multiple defects and unstable performance in the manufacturing of aircraft engine turbine disks have been solved, achieving efficient and low-cost material preparation and improving the strength and fatigue performance of the material.

CN120816098AActive Publication Date: 2025-10-21BEIJING SNECMA SAIC TURBOTECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510955521.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-10-21
Estimated Expiration
2045-07-11

AI Technical Summary

Technical Problem

Traditional forging and powder metallurgy processes result in long manufacturing cycles, high costs, and low material utilization rates for aircraft engine turbine discs, while traditional additive manufacturing has problems such as coarse material structure, numerous defects, and unstable performance.

Method used

The arc wire feeding process is combined with ultrasonic assistance, nanoparticle composite and multi-directional micro-forging. A coating layer is formed on the surface of the base wire by electroplating, and ultrasonic-assisted arc wire feeding is performed. Then, multi-directional forging and heat treatment are performed to prepare aircraft engine turbine disk materials.

Benefits of technology

The strength and fatigue performance of the turbine disc have been significantly improved, the material density has reached 99.5%, the problems of coarse structure and many defects have been solved, and fast and efficient material preparation has been achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120816098A_ABST
    Figure CN120816098A_ABST
Patent Text Reader

Abstract

The invention discloses application of an electric arc wire feeding process in preparation of an aero-engine turbine disc material, and belongs to the technical field of aero-engine turbine disc manufacturing. GH4169 high-temperature alloy is selected as a matrix wire material, TiC nano particles and Al2O3 nano particles form a coating layer through an electroplating method, and a composite wire material is prepared; and an ultrasonic-assisted electric arc wire feeding additive process is carried out, an ultrasonic action area covers a molten pool and then is along a liquid / solid two-phase area, when the temperature of a deposition layer is reduced to a set temperature, multidirectional micro-forging in which vertical forging and horizontal forging are alternately carried out is carried out, and finally heat treatment is carried out, so that the aero-engine turbine disc material is obtained. Through the synergistic effect of ultrasonic-assisted arc wire feeding additive manufacturing, nano-particle composite reinforcement and synchronous multidirectional micro-forging, the technical problems that according to a traditional additive manufacturing aero-engine turbine disc material, the structure is thick and large, the number of defects is large, and the performance is unstable are successfully solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of manufacturing aero-engine turbine disks, and in particular to the application of an arc wire feeding process in the preparation of aero-engine turbine disk materials. Background Art

[0002] To forge and manufacture high-temperature alloy turbine disks, it is necessary to first smelt high-quality high-temperature alloy ingots, and then make blanks. By controlling the forging ratio and going through processes such as upsetting and drawing, the internal structure of the ingots can be improved, coarse columnar crystals and casting defects can be broken, and the density and uniformity of the material can be improved. The blanks are then heated to the appropriate temperature and forged using a mold to allow the metal to flow plastically under pressure to fill the mold cavity and form the approximate shape of the turbine disk. Subsequently, through multiple passes of precision forging, the design size and accuracy requirements are gradually achieved. Finally, heat treatment is performed to optimize the alloy structure and improve strength, hardness, fatigue resistance and other properties.

[0003] The powder metallurgy method of manufacturing high-temperature alloy turbine disks begins with powder preparation. The high-temperature alloy melt is broken into fine powder particles by atomization. The powder is screened and graded, then placed in a special bag, vacuum-sealed, and hot isostatically pressed. The powder is densified under high temperature and high pressure to form a blank close to the shape of the turbine disk. Hot extrusion or forging is then performed to further improve the structure and performance, refine the grains, and increase the density and uniformity of the material. Finally, heat treatment is performed to eliminate residual stress, optimize the structure, and ensure that the turbine disk meets the performance requirements.

[0004] However, the forging process is complicated, involving multiple heating, forging and heat treatment, resulting in a long processing cycle. It usually takes weeks or even months to manufacture a turbine disk. Moreover, during the forging process, a large amount of metal is removed due to processing allowances, flash, etc., resulting in low material utilization and serious waste. The long cycle and low utilization rate greatly increase the manufacturing cost. The high cost limits the research and development and production scale of aircraft engines, and hinders the application of new technologies and performance improvement.

[0005] Powder metallurgy processes place high demands on equipment and the environment. Powder preparation, hot isostatic pressing, and heat treatment require significant equipment investment, and strict process control increases production costs. Furthermore, powders are susceptible to contamination during the process, impacting product quality. Quality assurance requires additional testing and control steps, further increasing costs. While material utilization rates are higher than forging processes, the complexity of the equipment and process means overall costs remain high. Furthermore, the overall production cycle is long, making it difficult to quickly respond to aircraft engine R&D and production needs, hindering the rapid iteration and development of aircraft engine technology.

[0006] When using existing traditional additive manufacturing technology to prepare high-temperature alloy turbine disks, the alloy material only undergoes free melting, accumulation, cooling, and solidification processes, lacking dynamic deformation, which inevitably leads to alloy crystal recrystallization and growth, and a decrease in mechanical properties. At the same time, traditional additive processes are prone to generating residual stress during layer-by-layer accumulation, which is prone to deformation and crack initiation during service, affecting the fatigue life of the turbine disk.

[0007] The prior art CN101985167B discloses a casting process for a turbine assembly. The formed turbine disc and turbine blades are firmly connected, have good stability, and are firmly connected. The process steps are simple and the molding is direct, and there is basically no scrap during casting. However, it does not solve the technical problems of coarse structure, many defects, and unstable performance of traditional additive manufacturing aircraft engine turbine disc materials. Summary of the Invention

[0008] The present invention discloses the application of arc wire feeding technology in the preparation of aero-engine turbine disk materials. Through the synergistic effect of ultrasonic-assisted arc wire feeding additive manufacturing, nano-particle composite reinforcement and synchronous multi-directional micro-forging, it successfully solves the technical problems of coarse structure, multiple defects and unstable performance of aero-engine turbine disk materials manufactured by traditional additive manufacturing.

[0009] The application of the arc wire feeding process of the present invention in the preparation of aircraft engine turbine disk materials is as follows: GH4169 high-temperature alloy is selected as the base wire material, a precursor is formed into a coating layer by electroplating to obtain a composite wire material, an ultrasonic-assisted arc wire feeding additive process is performed, the ultrasonic action area covers the liquid / solid two-phase region at the rear edge of the molten pool, and when the temperature of the deposited layer drops to a set temperature, multi-directional micro-forging is performed by alternating vertical forging and horizontal forging, and finally heat treatment is performed to obtain the aircraft engine turbine disk material.

[0010] As a further improvement of the present invention, the following steps are included:

[0011] S1. Preparation of composite wire: GH4169 high-temperature alloy was selected as the base wire, and the precursor was electroplated to form a coating layer on the wire surface to obtain a composite wire;

[0012] The precursor includes TiC nanoparticles and Al2O3 nanoparticles;

[0013] The TiC nanoparticles are composed of titanium powder and graphite powder, and the coating matrix is ​​a nickel-based binder;

[0014] S2. Ultrasonic-assisted arc wire feeding additive process: Arc wire feeding additive process is performed on composite wire. Ultrasonic waves are activated after the arc is struck, and the ultrasonic action area covers the liquid / solid two-phase region at the trailing edge of the molten pool.

[0015] S3. Synchronous multi-directional micro-forging: When the temperature of the deposited layer drops to the set temperature, multi-directional forging begins;

[0016] The multi-directional forging system includes vertical forging and horizontal forging;

[0017] S4. Heat treatment process: perform solution treatment, aging treatment and stress relief to obtain aircraft engine turbine disk material.

[0018] As a further improvement of the present invention, the content of the precursor accounts for 0.5% to 2.0% of the total mass of the composite wire.

[0019] As a further improvement of the present invention, in the arc wire feeding additive process, the interlayer temperature is controlled to be 150-250° C. and the deposition speed is 3-6 mm / s.

[0020] As a further improvement of the present invention, the current of the arc wire feeding additive process is 280-350A, the voltage is 24-28V, and the wire feeding speed is 4-8m / min.

[0021] As a further improvement of the present invention, the ultrasonic frequency of the ultrasonic wave is 40-60kHz, and the power density is 1.2-1.8W / cm 2 .

[0022] As a further improvement of the present invention, the forging frequency of the multi-directional forging is 10 to 15 times per minute, each forging lasts 0.1 to 0.3 seconds, and the forging direction is 90° vertical forging and 0° horizontal forging in a ratio of 2:1 alternatingly performed.

[0023] As a further improvement of the present invention, the 90° vertical forging pressure of the multi-directional forging system is 15-25 MPa, and the 0° horizontal forging pressure is 10-20 MPa.

[0024] As a further improvement of the present invention, the forging head material used in the multi-directional forging system is H13 hot working die steel with a hardness of HRC48-52. The forging head is cylindrical in shape with a diameter of 20-30 mm. The forging force loading rate is 50-100 MPa / s and the unloading rate is 20-50 MPa / s.

[0025] As a further improvement of the present invention, the present invention specifically comprises the following steps:

[0026] S1. Preparation of composite wire: GH4169 high-temperature alloy with a diameter of 1.2 mm was selected as the base wire. The precursor was electroplated to form a coating layer with a thickness of 5-15 μm on the surface of the wire to obtain the composite wire. The precursor content accounted for 0.5% to 2.0% of the total mass of the composite wire.

[0027] The precursor is composed of TiC nanoparticles with a particle size of 20-50nm and Al2O3 nanoparticles with a particle size of 30-80nm;

[0028] The TiC nanoparticles are composed of titanium powder with a particle size of less than 5 μm and graphite powder with a particle size of less than 2 μm in a molar ratio of 1:1, and the coating matrix is ​​a nickel-based binder with a thickness of 2-5 μm;

[0029] S2. Ultrasonic-assisted arc wire feeding additive process: Arc wire feeding additive process is performed on composite wire. Ultrasonic waves are activated after the arc is struck. The ultrasonic action area covers the liquid / solid two-phase region at the rear edge of the molten pool. The interlayer temperature is controlled at 150-250°C and the deposition rate is 3-6 mm / s.

[0030] The arc wire feeding additive process has a current of 280-350A, a voltage of 24-28V, and a wire feeding speed of 4-8m / min;

[0031] The ultrasonic frequency is 40-60kHz and the power density is 1.2-1.8W / cm 2 ;

[0032] S3. Synchronous multi-directional micro-forging: When the temperature of the deposited layer drops to 800-900°C, multi-directional forging begins. The forging frequency is 10-15 times / minute, and each forging lasts 0.1-0.3 seconds. The forging direction is 90° forging and 0° forging in a ratio of 2:1.

[0033] The vertical forging pressure of the multi-directional forging system is 15-25 MPa, and the horizontal forging pressure is 10-20 MPa;

[0034] The forging head used in the multi-directional forging system is made of H13 hot working die steel with a hardness of HRC48-52. The forging head is cylindrical with a diameter of 20-30 mm. The forging force loading rate is 50-100 MPa / s and the unloading rate is 20-50 MPa / s.

[0035] S4. Heat treatment process: Solution treatment is performed at 1065°C for 1 hour, air cooling, and then aging treatment is performed at 720°C for 8 hours, furnace cooling to 620°C for 8 hours, air cooling, and then stress relief is performed at 650°C for 3 hours, air cooling, to obtain the aircraft engine turbine disk material.

[0036] The present invention has the following beneficial effects:

[0037] (1) The present invention significantly improves the strength of aircraft engine turbine disks through the synergistic effects of nanoparticle composite reinforcement, ultrasonic-assisted fine grain strengthening, and multi-directional forging densification.

[0038] (2) The present invention promotes the homogenization of the molten pool through the ultrasonic acoustic streaming effect and eliminates interlayer defects and pores through multi-directional forging, effectively solving the problem of insufficient fatigue performance of traditional additive manufacturing materials.

[0039] (3) The present invention refines the grain size through the cavitation effect and acoustic streaming effect generated by ultrasonic frequency, and increases the material density to more than 99.5% through synchronous multi-directional micro-forging, eliminating the technical problems of coarse organization and many defects in traditional additive manufacturing.

[0040] (4) The present invention provides dispersion strengthening through TiC and Al2O3 nanoparticles, achieves fine grain strengthening with ultrasonic assistance, and ensures microstructure densification through multi-directional forging. The organic combination of the three strengthening mechanisms produces a synergistic effect and improves the mechanical properties of the material.

[0041] (5) The present invention reduces the standard deviation of mechanical properties in the manufacturing process by precisely controlling the interlayer temperature at 150-250°C, the forging frequency at 10-15 times / min, and the vertical forging pressure at 15-25 MPa, thus providing reliable technical support for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Schematic diagram of synchronous multi-directional micro-forging by arc wire feeding additive process in Example 1 of the present application;

[0043] Figure 2 Schematic diagram of a wire feeding device for the arc wire feeding additive process in Example 1 of the present application;

[0044] Figure 3 This is a schematic diagram of the forging head used in the multi-directional forging system in Example 1 of the present application. DETAILED DESCRIPTION

[0045] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0046] Example 1

[0047] GH4169 high-temperature alloy with a diameter of 1.2 mm was selected as the base wire. When preparing the precursor, TiC nanoparticles with a particle size of 25 nm and Al2O3 nanoparticles with a particle size of 35 nm were mixed in a mass ratio of 1:1, wherein the TiC nanoparticles were prepared by titanium powder with a particle size of 3 μm and graphite powder with a particle size of 1.5 μm in a molar ratio of 1:1, and coated with a nickel-based binder with a thickness of 3 μm. A coating layer with a thickness of 8 μm was formed on the surface of the base wire by electroplating. The precursor content accounted for 1.0% of the total mass of the composite wire to obtain a composite wire.

[0048] The composite wire is subjected to arc wire feeding additive process (the schematic diagram of the wire feeding device used in the arc wire feeding additive process is as follows Figure 2 As shown in the figure), set the current to 300A, voltage to 25V, wire feeding speed to 5m / min, control the interlayer temperature to 180℃, deposition speed to 4mm / s, start the ultrasonic wave after the arc is struck, the ultrasonic frequency to 45kHz, and the power density to 1.4W / cm 2 The ultrasonic action area covers the liquid-solid two-phase region at the rear edge of the molten pool.

[0049] When the temperature of the deposited layer drops to 850°C, multi-directional forging begins (the schematic diagram of the arc wire feeding additive process with synchronous multi-directional micro-forging is shown in Figure 2). Figure 1 As shown in the figure), the forging frequency is 12 times / minute, each forging duration is 0.2 seconds, the forging direction is 90° forging and 0° forging in a ratio of 2:1, the vertical forging pressure is 20MPa, the horizontal forging pressure is 15MPa, and a 25mm diameter H13 hot working die steel forging head is used (the schematic diagram of the forging head used in the multi-directional forging system is shown in the figure). Figure 3 As shown), hardness HRC50, forging force loading rate 75MPa / s, unloading rate 35MPa / s.

[0050] After forging, solution treatment is performed, the material is kept at 1065°C for 1 hour and air-cooled, followed by aging treatment, which is kept at 720°C for 8 hours, furnace cooled to 620°C, kept at this temperature for 8 hours and air-cooled, and finally stress relief is performed, which is kept at 650°C for 3 hours and air-cooled to obtain the aircraft engine turbine disk material.

[0051] Example 2

[0052] GH4169 high-temperature alloy with a diameter of 1.2 mm was selected as the base wire. When preparing the precursor, TiC nanoparticles with a particle size of 30 nm and Al2O3 nanoparticles with a particle size of 40 nm were mixed in a mass ratio of 1.2:1, wherein the TiC nanoparticles were prepared by titanium powder with a particle size of 2.5 μm and graphite powder with a particle size of 1 μm in a molar ratio of 1:1, and coated with a nickel-based binder with a thickness of 4 μm. A coating layer with a thickness of 12 μm was formed on the surface of the base wire by electroplating. The precursor content accounted for 1.5% of the total mass of the composite wire to obtain a composite wire.

[0053] The composite wire was subjected to arc wire feeding additive process with the current set to 320A, voltage to 26V, wire feeding speed to 6m / min, interlayer temperature to 200℃, deposition speed to 5mm / s, and ultrasonic wave started after arcing, with ultrasonic frequency of 50kHz and power density of 1.6W / cm 2 The ultrasonic action area covers the liquid-solid two-phase region at the rear edge of the molten pool.

[0054] When the temperature of the deposited layer drops to 880°C, multi-directional forging begins with a forging frequency of 13 times / minute and a forging duration of 0.25 seconds each time. The forging direction is 90° forging and 0° forging, alternating in a ratio of 2:1. The vertical forging pressure is 22 MPa and the horizontal forging pressure is 18 MPa. A 28 mm diameter H13 hot work die steel forging head with a hardness of HRC51 is used. The forging force loading rate is 85 MPa / s and the unloading rate is 40 MPa / s.

[0055] After forging, solution treatment is performed, the material is kept at 1065°C for 1 hour and air-cooled, followed by aging treatment, which is kept at 720°C for 8 hours, furnace cooled to 620°C, kept at this temperature for 8 hours and air-cooled, and finally stress relief is performed, which is kept at 650°C for 3 hours and air-cooled to obtain the aircraft engine turbine disk material.

[0056] Example 3

[0057] GH4169 high-temperature alloy with a diameter of 1.2 mm was selected as the base wire. When preparing the precursor, TiC nanoparticles with a particle size of 20 nm and Al2O3 nanoparticles with a particle size of 30 nm were mixed in a mass ratio of 0.8:1, wherein the TiC nanoparticles were prepared by titanium powder with a particle size of 4 μm and graphite powder with a particle size of 1.8 μm in a molar ratio of 1:1, and coated with a nickel-based binder with a thickness of 2 μm. A coating layer with a thickness of 5 μm was formed on the surface of the base wire by electroplating. The precursor content accounted for 0.5% of the total mass of the composite wire to obtain a composite wire.

[0058] The composite wire was subjected to arc wire feeding additive process with the current set to 280A, voltage to 24V, wire feeding speed to 4m / min, interlayer temperature to 150℃, deposition speed to 3mm / s, and ultrasonic wave started after arcing, with ultrasonic frequency of 40kHz and power density of 1.2W / cm 2 The ultrasonic action area covers the liquid-solid two-phase region at the rear edge of the molten pool.

[0059] When the temperature of the deposited layer drops to 800°C, multi-directional forging begins with a forging frequency of 10 times / minute and a forging duration of 0.1 second each time. The forging direction is 90° forging and 0° forging, alternating in a ratio of 2:1. The vertical forging pressure is 15 MPa and the horizontal forging pressure is 10 MPa. A 20 mm diameter H13 hot work die steel forging head with a hardness of HRC48 is used. The forging force loading rate is 50 MPa / s and the unloading rate is 20 MPa / s.

[0060] After forging, solution treatment is performed, the material is kept at 1065°C for 1 hour and air-cooled, followed by aging treatment, which is kept at 720°C for 8 hours, furnace cooled to 620°C, kept at this temperature for 8 hours and air-cooled, and finally stress relief is performed, which is kept at 650°C for 3 hours and air-cooled to obtain the aircraft engine turbine disk material.

[0061] Example 4

[0062] GH4169 high-temperature alloy with a diameter of 1.2 mm was selected as the base wire. When preparing the precursor, TiC nanoparticles with a particle size of 45 nm and Al2O3 nanoparticles with a particle size of 70 nm were mixed in a mass ratio of 1.5:1, wherein the TiC nanoparticles were prepared by titanium powder with a particle size of 4.5 μm and graphite powder with a particle size of 1.2 μm in a molar ratio of 1:1, and coated with a nickel-based binder with a thickness of 4.5 μm. A coating layer with a thickness of 14 μm was formed on the surface of the base wire by electroplating. The precursor content accounted for 1.8% of the total mass of the composite wire to obtain a composite wire.

[0063] The composite wire was subjected to arc wire feeding additive process with the current set to 340A, voltage to 27V, wire feeding speed to 7m / min, interlayer temperature to 230℃, deposition speed to 5.5mm / s, and ultrasonic wave started after arcing, with ultrasonic frequency of 55kHz and power density of 1.7W / cm 2 The ultrasonic action area covers the liquid-solid two-phase region at the rear edge of the molten pool.

[0064] When the temperature of the deposited layer drops to 870°C, multi-directional forging begins with a forging frequency of 14 times / minute and a forging duration of 0.28 seconds each time. The forging direction is 90° forging and 0° forging, alternating in a ratio of 2:1. The vertical forging pressure is 24 MPa and the horizontal forging pressure is 19 MPa. A 27 mm diameter H13 hot work die steel forging head with a hardness of HRC51 is used. The forging force loading rate is 90 MPa / s and the unloading rate is 45 MPa / s.

[0065] After forging, solution treatment is performed, the material is kept at 1065°C for 1 hour and air-cooled, followed by aging treatment, which is kept at 720°C for 8 hours, furnace cooled to 620°C, kept at this temperature for 8 hours and air-cooled, and finally stress relief is performed, which is kept at 650°C for 3 hours and air-cooled to obtain the aircraft engine turbine disk material.

[0066] Example 5

[0067] GH4169 high-temperature alloy with a diameter of 1.2 mm was selected as the base wire. When preparing the precursor, TiC nanoparticles with a particle size of 50 nm and Al2O3 nanoparticles with a particle size of 80 nm were mixed in a mass ratio of 1:1.2, wherein the TiC nanoparticles were prepared from titanium powder with a particle size of 5 μm and graphite powder with a particle size of 2 μm in a molar ratio of 1:1, and coated with a nickel-based binder with a thickness of 5 μm. A coating layer with a thickness of 15 μm was formed on the surface of the base wire by electroplating. The precursor content accounted for 2.0% of the total mass of the composite wire to obtain a composite wire.

[0068] The composite wire was subjected to arc wire feeding additive process with current of 350A, voltage of 28V, wire feeding speed of 8m / min, interlayer temperature of 250℃, deposition speed of 6mm / s, and ultrasonic wave was started after arcing with ultrasonic frequency of 60kHz and power density of 1.8W / cm 2 The ultrasonic action area covers the liquid-solid two-phase region at the rear edge of the molten pool.

[0069] When the temperature of the deposited layer drops to 900°C, multi-directional forging begins with a forging frequency of 15 times / minute and a forging duration of 0.3 seconds each time. The forging direction is 90° forging and 0° forging, alternating in a ratio of 2:1. The vertical forging pressure is 25 MPa, the horizontal forging pressure is 20 MPa, and a 30 mm diameter H13 hot work die steel forging head with a hardness of HRC52 is used. The forging force loading rate is 100 MPa / s and the unloading rate is 50 MPa / s.

[0070] After forging, solution treatment is performed, the material is kept at 1065°C for 1 hour and air-cooled, followed by aging treatment, which is kept at 720°C for 8 hours, furnace cooled to 620°C, kept at this temperature for 8 hours and air-cooled, and finally stress relief is performed, which is kept at 650°C for 3 hours and air-cooled to obtain the aircraft engine turbine disk material.

[0071] Comparative Example 1 is different from Example 1 in that there is no ultrasonic assistance in the arc wire feeding additive process.

[0072] GH4169 high-temperature alloy with a diameter of 1.2 mm was selected as the base wire. When preparing the precursor, TiC nanoparticles with a particle size of 25 nm and Al2O3 nanoparticles with a particle size of 35 nm were mixed in a mass ratio of 1:1, wherein the TiC nanoparticles were prepared by titanium powder with a particle size of 3 μm and graphite powder with a particle size of 1.5 μm in a molar ratio of 1:1, and coated with a nickel-based binder with a thickness of 3 μm. A coating layer with a thickness of 8 μm was formed on the surface of the base wire by electroplating. The precursor content accounted for 1.0% of the total mass of the composite wire to obtain a composite wire.

[0073] The composite wire was subjected to a conventional arc wire feeding additive process with current set to 300 A, voltage to 25 V, wire feeding speed to 5 m / min, interlayer temperature to 180 °C, deposition speed to 4 mm / s. The ultrasonic system was not started during the entire additive process.

[0074] When the temperature of the deposited layer drops to 850°C, multi-directional forging begins with a forging frequency of 12 times / minute and a forging duration of 0.2 seconds each time. The forging direction is 90° forging and 0° forging, alternating in a ratio of 2:1. The vertical forging pressure is 20 MPa and the horizontal forging pressure is 15 MPa. A 25 mm diameter H13 hot work die steel forging head with a hardness of HRC50 is used. The forging force loading rate is 75 MPa / s and the unloading rate is 35 MPa / s.

[0075] After forging, solution treatment is performed, the material is kept at 1065°C for 1 hour and air-cooled, followed by aging treatment, which is kept at 720°C for 8 hours, furnace cooled to 620°C, kept at this temperature for 8 hours and air-cooled, and finally stress relief is performed, which is kept at 650°C for 3 hours and air-cooled to obtain the aircraft engine turbine disk material.

[0076] Comparative Example 2 differs from Example 1 in that no synchronous multi-directional forging is performed.

[0077] GH4169 high-temperature alloy with a diameter of 1.2 mm was selected as the base wire. When preparing the precursor, TiC nanoparticles with a particle size of 25 nm and Al2O3 nanoparticles with a particle size of 35 nm were mixed in a mass ratio of 1:1, wherein the TiC nanoparticles were prepared by titanium powder with a particle size of 3 μm and graphite powder with a particle size of 1.5 μm in a molar ratio of 1:1, and coated with a nickel-based binder with a thickness of 3 μm. A coating layer with a thickness of 8 μm was formed on the surface of the base wire by electroplating. The precursor content accounted for 1.0% of the total mass of the composite wire to obtain a composite wire.

[0078] The composite wire was subjected to arc wire feeding additive process with the current set to 300A, voltage to 25V, wire feeding speed to 5m / min, interlayer temperature to 180℃, deposition speed to 4mm / s, and ultrasonic wave to be started after arcing, with ultrasonic frequency of 45kHz and power density of 1.4W / cm 2 The ultrasonic action area covers the liquid-solid two-phase region at the rear edge of the molten pool.

[0079] After the addition is completed, heat treatment is carried out directly without any forging process. Solution treatment is carried out, and the material is kept at 1065℃ for 1 hour and air-cooled. Then, aging treatment is carried out, and the material is kept at 720℃ for 8 hours, furnace cooled to 620℃, kept at 8 hours and air-cooled. Finally, stress relief is carried out, and the material is kept at 650℃ for 3 hours and air-cooled to obtain the aircraft engine turbine disk material.

[0080] Comparative Example 3 is different from Example 1 in that the wire is not reinforced with nanoparticles.

[0081] Pure GH4169 high-temperature alloy with a diameter of 1.2 mm was selected as the wire without adding any precursor or nanoparticle reinforcement phase.

[0082] The wire was subjected to arc wire feeding additive process, with current set to 300A, voltage to 25V, wire feeding speed to 5m / min, interlayer temperature to 180℃, deposition speed to 4mm / s, and ultrasonic wave started after arcing, with ultrasonic frequency to 45kHz and power density to 1.4W / cm 2 The ultrasonic action area covers the liquid-solid two-phase region at the rear edge of the molten pool.

[0083] When the temperature of the deposited layer drops to 850°C, multi-directional forging begins with a forging frequency of 12 times / minute and a forging duration of 0.2 seconds each time. The forging direction is 90° forging and 0° forging, alternating in a ratio of 2:1. The vertical forging pressure is 20 MPa and the horizontal forging pressure is 15 MPa. A 25 mm diameter H13 hot work die steel forging head with a hardness of HRC50 is used. The forging force loading rate is 75 MPa / s and the unloading rate is 35 MPa / s.

[0084] After forging, solution treatment is performed, the material is kept at 1065°C for 1 hour and air-cooled, followed by aging treatment, which is kept at 720°C for 8 hours, furnace cooled to 620°C, kept at this temperature for 8 hours and air-cooled, and finally stress relief is performed, which is kept at 650°C for 3 hours and air-cooled to obtain the aircraft engine turbine disk material.

[0085] Performance testing

[0086] Tensile properties test: Standard tensile specimens were prepared according to GB / T 228.1-2010. The gauge section diameter of the specimens was 5 mm and the gauge length was 25 mm. Tensile tests were performed using a universal testing machine at room temperature at a tensile rate of 2 mm / min. The yield strength, tensile strength, and elongation were recorded. Five specimens were tested in each group, and the average value was taken.

[0087] Hardness test: Vickers hardness tester was used in accordance with GB / T 4340.1-2009 standard. The load force was 98N and the load holding time was 15 seconds. Ten test points were randomly selected on the sample surface and the average value was taken. The sample surface was ground and polished before testing, and the roughness Ra was not greater than 0.1μm.

[0088] Impact toughness test: V-notch impact specimens were prepared in accordance with GB / T 229-2020. The specimen dimensions were 10 mm x 10 mm x 55 mm, and the notch depth was 2 mm. Pendulum impact testing was performed at room temperature. Three specimens were tested in each group, and the average value was taken. The test should be completed within 24 hours before testing after specimen processing.

[0089] Fatigue performance test: Fatigue test was carried out using a rotary bending fatigue testing machine in accordance with GB / T 4337-2015 standard. The specimen diameter was 7.5 mm, the surface roughness Ra was not greater than 0.4 μm, the stress ratio R was -1, the frequency was 50 Hz, and the test environment temperature was 20°C.

[0090] Table 1. Mechanical properties test results

[0091] sample Yield strength (MPa) Tensile strength (MPa) Elongation (%) Vickers hardness (HV) Example 1 1245 1485 18.5 425 Example 2 1268 1502 17.8 438 Example 3 1198 1422 19.2 405 Example 4 1289 1518 17.1 445 Example 5 1312 1534 16.8 452 Comparative Example 1 1086 1298 14.2 368 Comparative Example 2 1142 1356 15.8 385 Comparative Example 3 1025 1215 16.5 342

[0092] Table 2. Impact toughness and fatigue performance test results

[0093] sample <![CDATA[Impact toughness (J / cm 2 )]]> Fatigue limit (MPa) <![CDATA[Fatigue life (x10 6 times)]]> Example 1 85.2 685 2.85 Example 2 88.6 712 3.12 Example 3 82.1 658 2.58 Example 4 91.3 728 3.35 Example 5 94.7 745 3.52 Comparative Example 1 68.4 542 1.86 Comparative Example 2 72.8 578 2.14 Comparative Example 3 65.2 518 1.72

[0094] As can be seen from Table 1, the yield strengths of Examples 1-5 are significantly higher than those of the comparative examples, with the yield strength of Example 5 reaching 1312 MPa, 20.8% higher than that of Comparative Example 1, 14.9% higher than that of Comparative Example 2, and 28.0% higher than that of Comparative Example 3. In terms of tensile strength, the tensile strengths of the examples are generally in the range of 1420-1540 MPa, while those of the comparative examples are only in the range of 1215-1356 MPa. The tensile strength of Example 5 is 1534 MPa, which is 18.2% higher than that of Comparative Example 1. The Vickers hardness test shows that the hardness values ​​of the examples all exceed 400 HV, with Example 5 reaching 452 HV, while the hardness values ​​of the comparative examples are all below 390 HV, indicating that the synergistic effect of the composite reinforcement phase, ultrasonic assistance, and multi-directional forging significantly improves the strength and hardness of the material. This is due to the combined effects of the dispersion strengthening effect of nanoparticles, ultrasonic grain refinement, and multi-directional forging to eliminate defects and improve tissue density, indicating that the technical solution of the present invention can significantly improve the static mechanical properties of the material.

[0095] As can be seen from Table 2, the examples show obvious advantages in terms of impact toughness. The impact toughness of Example 5 reaches 94.7 J / cm 2 , which is 38.5% higher than that of comparative example 1, 30.0% higher than that of comparative example 2, and 45.2% higher than that of comparative example 3. In terms of fatigue limit, Example 5 reaches 745MPa, which is 37.5% higher than that of comparative example 1, 28.9% higher than that of comparative example 2, and 43.8% higher than that of comparative example 3. Fatigue life test shows that the fatigue life of Example 5 under the same stress level reaches 3.52x10 6 times, which is 89.2% higher than that of comparison example 1, 64.5% higher than that of comparison example 2, and 104.7% higher than that of comparison example 3, indicating that ultrasonic assistance can effectively refine grains and reduce inclusions, multi-directional forging can eliminate porosity defects and improve the uniformity of the internal structure of the material, and the nano-reinforced phase improves the fatigue resistance of the material by preventing crack propagation. This is because the ultrasonic sound streaming effect promotes the stirring of the molten pool and improves the uniformity of element distribution. The compaction effect of multi-directional forging eliminates the micropores and interlayer defects generated in the additive manufacturing process. Nanoparticles as the second phase reinforcement phase effectively prevent dislocation movement and crack propagation, indicating that the technical route of the present invention has significant advantages in improving the dynamic mechanical properties of materials.

[0096] This invention successfully addresses the technical challenges of conventional additive manufacturing of aeroengine turbine disk materials, such as coarse microstructure, numerous defects, and unstable performance, through the synergistic effects of ultrasonically assisted arc wire feeding, nanoparticle composite reinforcement, and simultaneous multi-directional micro-forging. Test results show that compared to the comparative example, the embodiment of the invention demonstrates significant improvements in key performance indicators such as yield strength, tensile strength, impact toughness, and fatigue performance, fully meeting the demanding requirements of aeroengine turbine disks and providing important technical support for the additive manufacturing of key high-performance aeroengine components.

[0097] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. The application of arc wire feeding technology in the preparation of aero-engine turbine disk materials is characterized by: By selecting GH4169 high-temperature alloy as the base wire, the precursor is formed into a coating layer by electroplating to produce a composite wire, and an ultrasonic-assisted arc wire feeding additive process is carried out. The ultrasonic action area covers the liquid / solid two-phase region at the trailing edge of the molten pool. When the temperature of the deposited layer drops to the set temperature, multi-directional micro-forging is performed by alternating vertical forging and horizontal forging. Finally, heat treatment is carried out to produce an aircraft engine turbine disk material.

2. The use according to claim 1, characterized in that The following steps are involved: S1. Preparation of composite wire: GH4169 high-temperature alloy was selected as the base wire, and the precursor was electroplated to form a coating layer on the wire surface to obtain a composite wire; The precursor includes TiC nanoparticles and Al2O3 nanoparticles; The TiC nanoparticles are composed of titanium powder and graphite powder, and the coating matrix is ​​a nickel-based binder; S2. Ultrasonic-assisted arc wire feeding additive process: Arc wire feeding additive process is performed on composite wire. Ultrasonic waves are activated after the arc is struck, and the ultrasonic action area covers the liquid / solid two-phase region at the trailing edge of the molten pool. S3. Synchronous multi-directional micro-forging: When the temperature of the deposited layer drops to the set temperature, multi-directional forging begins; The multi-directional forging system includes vertical forging and horizontal forging; S4. Heat treatment process: perform solution treatment, aging treatment and stress relief to obtain aircraft engine turbine disk material.

3. The use according to claim 2, characterized in that The content of the precursor accounts for 0.5% to 2.0% of the total mass of the composite wire.

4. The use according to claim 2, characterized in that In the arc wire feeding additive process, the interlayer temperature is controlled at 150-250° C. and the deposition speed is controlled at 3-6 mm / s.

5. The use according to claim 2, characterized in that The arc wire feeding additive process has a current of 280 to 350 A, a voltage of 24 to 28 V, and a wire feeding speed of 4 to 8 m / min.

6. The use according to claim 2, characterized in that The ultrasonic frequency of the ultrasonic wave is 40-60kHz, and the power density is 1.2-1.8W / cm 2 .

7. The use according to claim 2, characterized in that The multi-directional forging has a forging frequency of 10 to 15 times per minute, each forging lasts for 0.1 to 0.3 seconds, and the forging directions are 90° vertical forging and 0° horizontal forging in a ratio of 2:1, which are performed alternately.

8. The use according to claim 2, characterized in that The multi-directional forging system has a 90° vertical forging pressure of 15-25 MPa and a 0° horizontal forging pressure of 10-20 MPa.

9. The use according to claim 2, characterized in that The forging head used in the multi-directional forging system is made of H13 hot working die steel with a hardness of HRC48-52. The forging head is cylindrical with a diameter of 20-30 mm. The forging force loading rate is 50-100 MPa / s and the unloading rate is 20-50 MPa / s.

10. The use according to claim 2, characterized in that The specific steps include: S1. Preparation of composite wire: GH4169 high-temperature alloy with a diameter of 1.2 mm was selected as the base wire. The precursor was electroplated to form a coating layer with a thickness of 5-15 μm on the surface of the wire to obtain the composite wire. The precursor content accounted for 0.5% to 2.0% of the total mass of the composite wire. The precursor is composed of TiC nanoparticles with a particle size of 20-50nm and Al2O3 nanoparticles with a particle size of 30-80nm; The TiC nanoparticles are composed of titanium powder with a particle size of less than 5 μm and graphite powder with a particle size of less than 2 μm in a molar ratio of 1:1, and the coating matrix is ​​a nickel-based binder with a thickness of 2-5 μm; S2. Ultrasonic-assisted arc wire feeding additive process: Arc wire feeding additive process is performed on composite wire. Ultrasonic waves are activated after the arc is struck. The ultrasonic action area covers the liquid / solid two-phase region at the rear edge of the molten pool. The interlayer temperature is controlled at 150-250°C and the deposition rate is 3-6 mm / s. The arc wire feeding additive process has a current of 280-350A, a voltage of 24-28V, and a wire feeding speed of 4-8m / min; The ultrasonic frequency is 40-60kHz and the power density is 1.2-1.8W / cm 2 ; S3. Synchronous multi-directional micro-forging: When the temperature of the deposited layer drops to 800-900°C, multi-directional forging begins. The forging frequency is 10-15 times / minute, and each forging lasts 0.1-0.3 seconds. The forging direction is 90° forging and 0° forging in a ratio of 2:

1. The vertical forging pressure of the multi-directional forging system is 15-25 MPa, and the horizontal forging pressure is 10-20 MPa; The forging head used in the multi-directional forging system is made of H13 hot working die steel with a hardness of HRC48-52. The forging head is cylindrical with a diameter of 20-30 mm. The forging force loading rate is 50-100 MPa / s and the unloading rate is 20-50 MPa / s. S4. Heat treatment process: Solution treatment is performed at 1065°C for 1 hour, air cooling, and then aging treatment is performed at 720°C for 8 hours, furnace cooling to 620°C for 8 hours, air cooling, and then stress relief is performed at 650°C for 3 hours, air cooling, to obtain the aircraft engine turbine disk material.

Citation Information

Patent Citations

  • Casting technique of turbine assembly

    CN101985167B

  • CMT-ultrasonic vibration composite additive manufacturing method

    CN110480125A

  • Method for reducing internal residual stress of GH4169 alloy large-size disk forge piece

    CN110551955A

  • Systems and methods for additive manufacturing using aluminum metal-cored wire

    CN111715974A

  • Method for refining grains through laser fuse wire additive manufacturing

    CN115430841A